An Sn doped 1T–2H MoS2 few-layer structure embedded in N/P co-doped bio-carbon for high performance sodium-ion batteries. Issue 25 (8th March 2019) - Zeng, Lingxing; Luo, Fenqiang; Xia, Xinshu; Yang, Min-Quan; Xu, Lihong; Wang, Jianbiao; Feng, Xiaoshan; Qian, Qingrong; Wei, Mingdeng; Chen, Qinghua
Abstract : A facile route for fabrication of an Sn doped 1T–2H MoS2 few-layer structure embedded in N/P co-doped bio-carbon is initially developed using natural chlorella as an adsorbent and a nanoreactor. Abstract : A facile method for fabricating Sn doped 1T–2H MoS2 embedded in N/P co-doped bio-carbon is developed using natural chlorella as an adsorbent and a nanoreactor. When used as an anode for sodium-ion batteries, it delivers an excellent rate performance (167 mA h g −1 at 15 A g −1 ), high capacity (533 mA h g −1 after 50 cycles at 0.1 A g −1 ), and superior long-term cycling stability (320 mA h g −1 after 500 cycles at 1 A g −1 ) which are attributed to the synergistic effects of few-layer 1T–2H MoS2 moderate Sn doping and the N/P co-doped bio-carbon.